Pengembangan Buku Saku Digital Berbasis 3D Pageflip Professional Sebagai Media Pembelajaran yang Menarik dan Praktis Pada Materi Laju Reaksi - Saragih, Gita Geniati; Rasmiwetti, Rasmiwetti; Copriady, Jimmi (FKIP University of Mataram, 2024)
This developmental research aims to develop learning media as a digital pocketbook based on 3D Pageflip Professional on the valid Reaction Rate material. This type of research is research and development (R&D) with the ADDIE development model, which includes analysis, design, development, implementation, and evaluation. This research was carried out only until the development stage. The data analysis technique used in this study is descriptive statistics, namely by calculating the percentage of validation values. The data obtained came from validators consisting of 3 expert lecturers, respondents consisting of 2 chemistry teachers and 30 students from two high schools, SMA Negeri 4 and SMA Negeri 5 Pekanbaru. The results showed that the development of learning media in the form of a digital pocketbook on the Reaction Rate material was declared valid to meet the aspects of substance content, learning design, display (visual communication), software utilization with percentages of 90%, 98.21%, 93,75% respectively, 94.44%.. the overall average score of digital pocketbook validation is 94.1%. The results of the trial of user responses with teachers and students to digital pocketbooks showed that the reaction rates were 96.32% and 86.61%, respectively, with practical criteria by teacher respondents and interesting criteria by students.